LKPD PMRI DENGAN KONTEKS MAKANAN KHAS KOTA PALEMBANG UNTUK MENINGKATKAN HASIL BELAJAR - Syaifudin Syaifudin; Bonita Hirza; Luvi Antari; Ervina Mukharomah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
The low learning outcomes and student responses to teaching and learning activities is one of the problems in learning that must be addressed immediately. This article aims to look at improving learning outcomes in mathematics which is taught with Student Worksheets (LKPD) based on the PMRI approach using the traditional culinary context of South Sumatra. This type of research is Classroom Action Research (CAR). The research subjects were 28 grade IV students at an elementary school in Palembang. The research flow uses the Kemmis and Mc. Taggart plots, with the stages in this study namely planning, action, observation, and reflection which are carried out in two cycles. Data collection was in the form of tests to measure learning outcomes and attitude questionnaires used to determine student responses. Data analysis was carried out qualitatively and quantitatively. From the results of data analysis, it was obtained that the average student learning outcomes in cycle I was 70.82 with a percentage of student completeness of 57.14%, the average student learning outcomes in cycle II rose to 75.63 with a percentage of student completeness of 86.86%. While the results of the questionnaire showed that the activeness and enthusiasm of students increased. The conclusion is that learning mathematics taught with PMRI-based LKPD with the traditional culinary context of Palembang City can increase student interest and learning outcomes.